(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The concept of ‘Corporate Social Responsibility’ (CSR) has today become a key aspect of business philosophy and practice world over. CSR has been part of Indian business for long. There have been efforts, both in the remote and recent past, on the part of business community and government to make responsible business practices part of our business ethos. All the same, such efforts have been unsystematic, individual institution specific in orientation and, in certain cases, lacking a well-defined direction and purpose. Of late, there are indications that the scenario is changing. A host of factors such as globalization of business operations, the rise to prominence of climate change agenda, adoption of Millennium Development Goals and so on has contributed to an enhanced level of concern and commitment to the idea corporate social responsibility. As for the government’s initiatives are concerned, these are reflected in the new Companies Act passed in 2013, which mandates CSR spend for a defined category of corporate entities. This has given fillip to corporate CSR initiatives in a big way, which have, in many cases, gone beyond the requirements of the law. There have also been efforts, in tune with the global practice, to make CSR part of the corporate strategy and as a tool for attaining and sustaining competitive edge in the market place. The proposed paper will trace the evolution of CSR in India, Government initiatives to make CSR a part of corporate functioning in the country and the emerging trends in Indian business sector which look at CSR as a tool for competitive strategy.